2015
DOI: 10.1021/jacs.5b07119
|View full text |Cite
|
Sign up to set email alerts
|

A Designed Metalloenzyme Achieving the Catalytic Rate of a Native Enzyme

Abstract: Terminal oxidases catalyze four-electron reduction of oxygen to water, and the energy harvested is utilized to drive the synthesis of adenosine triphosphate. While much effort has been made to design a catalyst mimicking the function of terminal oxidases, most biomimetic catalysts have much lower activity than native oxidases. Herein we report a designed oxidase in myoglobin with an O2 reduction rate (52 s–1) comparable to that of a native cytochrome (cyt) cbb3 oxidase (50 s–1) under identical conditions. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 54 publications
0
77
0
Order By: Relevance
“…b 5 ), the G65Y-Cu B Mb variant was shown to reduce oxygen with rates (52 s −1 ) comparable to a native C c O (50 s −1 ). 228 Moreover, when the designed protein was immobilized onto electrodes, the electrocatalytic reduction of oxygen using G65Y-Cu B Mb not only resulted in very selective oxygen reduction (~ 96% water) but also exhibited rates (5000 s −1 ) exceeding the fastest CcO (bovine CcO with rates of 500 s −1 ). 229 These results demonstrated that it is possible to redesign the metal-binding sites in native scaffolds that display new functions (e.g., from reversible O 2 binding in WTMb to catalytic O 2 reduction to H 2 O) that can meet or even exceed the catalytic efficiency of native enzymes.…”
Section: Artificial Oxygen-activating Metalloenzymes By Protein Rementioning
confidence: 99%
“…b 5 ), the G65Y-Cu B Mb variant was shown to reduce oxygen with rates (52 s −1 ) comparable to a native C c O (50 s −1 ). 228 Moreover, when the designed protein was immobilized onto electrodes, the electrocatalytic reduction of oxygen using G65Y-Cu B Mb not only resulted in very selective oxygen reduction (~ 96% water) but also exhibited rates (5000 s −1 ) exceeding the fastest CcO (bovine CcO with rates of 500 s −1 ). 229 These results demonstrated that it is possible to redesign the metal-binding sites in native scaffolds that display new functions (e.g., from reversible O 2 binding in WTMb to catalytic O 2 reduction to H 2 O) that can meet or even exceed the catalytic efficiency of native enzymes.…”
Section: Artificial Oxygen-activating Metalloenzymes By Protein Rementioning
confidence: 99%
“…b 5 (Figure 8a) reduced oxygen at a rate (52 s −1 ) comparable to that of a native HCO (cyt. cbb 3 oxidase, 50 s −1 )(Yu et al, 2015). …”
Section: Step 4: Further Improvement Of Designed Heteronuclear Metallmentioning
confidence: 99%
“…© 2014 American Chemical Society (c) Enhancement of binding affinity and catalytic efficiency of MnC c P mimics by mutation secondary coordination sphere residues. Figures are adapted with permission from ref (Yu et al, 2015), (Bhagi-Damodaran et al, 2014) and (Hosseinzadeh et al, 2016) respectively.…”
Section: Figurementioning
confidence: 99%
“…By incorporating a copper binding site and changing the electrostatics of the solvent accessible sites, the L29H/F43H/G65Y and D44K/D60K/E85K mutant of myoglobin transformed the oxygen storage protein into a robust oxidase with dramatic enhanced functionality. A few such studies incorporated a Cu B site in myoglobin in order to provide insight into the mechanism of reduction of dioxygen by heme-copper oxidases [8,[51][52][53][54]. In this way, myoglobin serves as a small model protein that mimics the large membrane-bound heme-copper oxidase.…”
Section: Oxidase Activitymentioning
confidence: 99%